Welfare Regime Transformation in Indonesia: A Citizenship Debate - Yuda, Tauchid Komara (UI Scholars Hub, 2018)
This article discusses the outlook for the Indonesian welfare regime using citizenship as a framework. I argue that the transformation of the Indonesian welfare regime from productivist characteristics to universalism has been disrupted by the discourse of communitarian and market citizenship that have become dependent on the welfare configuration path in contemporary Indonesia. This circumstance has become an endogenous factor that obstructs innovation and change within an administrative body of universal social protection. Using evidence from Indonesian experiences, this article can help develop a further understanding of the complexity of relationships between welfare provision and citizenship in the context of developing countries.